Sonohysterography in the study of infertility. - Álvarez, Guillermo (2015)
OBJECTIVE: Value of sonohysterography in the study of infertility. MATERIAL: Fifteen infertile patients studied with hysterosalpingography and sonohysterogrraphy. METHOD: Filling of uterine cavity with sterile saline solution, through a catheter and under sonographic control. RESULTS: Sonohysterography permits better differentiation of endometrium and myometrium during the menstrual cycle. In uterine alterations it precises intracavitary lesions better than usual endosonography: endometrial polyps and sinequiae, submucous myoma or endometrial carcinoma. CONCLUSION: Sonohysterography constitutes a valuable procedure in endometrial and submucous intracavitary alterations differentiation, is a fast and low cost exploration and does not require contrast media or ionizing radiations.